Development and characterization of ferret ex vivo tracheal injury and cell engraftment model - Ievlev, Vitaly; Pai, Albert C.; Dillon, Drew S.; Kuhl, Spencer; Lynch, Thomas J.; Freischlag, Kyle W.; Gries, Caitlyn B.; Engelhardt, John F.; Parekh, Kalpaj R. (Frontiers in Medicine, 2023)
The field of airway biology research relies primarily on in vitro and in vivo models of disease and injury. The use of ex vivo models to study airway injury and cell-based therapies remains largely unexplored although such models have the potential to overcome certain limitations of working with live animals and may more closely replicate in vivo processes than in vitro models can. Here, we characterized a ferret ex vivo tracheal injury and cell engraftment model. We describe a protocol for whole-mount staining of cleared tracheal explants, and showed that it provides a more comprehensive structural overview of the surface airway epithelium (SAE) and submucosal glands (SMGs) than 2D sections, revealing previously underappreciated structural anatomy of tracheal innervation and vascularization. Using an ex vivo model of tracheal injury, we evaluated the injury responses in the SAE and SMGs that turned out to be consistent with published in vivo work. We used this model to assess factors that influence engraftment of transgenic cells, providing a system for optimizing cell-based therapies. Finally, we developed a novel 3D-printed reusable culture chamber that enables live imaging of tracheal explants and differentiation of engrafted cells at an air-liquid interface. These approaches promise to be useful for modeling pulmonary diseases and testing therapies. Graphical abstract 1,2. We describe here a method for differential mechanical injury of ferret tracheal explants that can be used to evaluate airway injury responses ex vivo. 3. Injured explants can be cultured at ALI (using the novel tissue-transwell device on the right) and submerged long-term to evaluate tissue-autonomous regeneration responses. 4. Tracheal explants can also be used for low throughput screens of compounds to improve cell engraftment efficiency or can be seeded with particular cells to model a disease phenotype. 5. Lastly, we demonstrate that ex vivo-cultured tracheal explants can be evaluated by various molecular assays and by immunofluorescent imaging that can be performed live using our custom-designed tissue-transwell.